Eficiência alimentar, características da carcaça e qualidade da carne de cordeiros alimentados com volumoso e/ou concentrado - Lopes, Jusecléia Ferreira (2014)
It was evaluated nutrient consumption, performance and feed efficiency (Chapter I), quantitative and qualitative carcass traits, tissue composition (chapter II), physico-chemical instrumental analyzes the meat (chapter III), fatty acids profile and the sensory the meat (chapter IV) of males and females lambs finished in feedlot diets fed with forage and / or concentrate. The experiment completely randomized design factorial 3 x 2 (three diets x 2 sexes) with five repetições. Foram used 30 weaned lambs, 15 uncastrated male and 15 females. The experimental diets were: 100% 0% forage and concentrate (100:0), 50% forage and 50% concentrate (50:50) 0% 100% forage and concentrate (0:100). The animals were slaughtered when they approached the corporal condition 3.0. The lambs fed diets 100:0 had a greater dry matter intake (DMI), and the AVE diet lower consumption. The slaughter weight was higher than in the diet 100:0, which differed from the 50:50 diet (P <0.05), but these were similar to diet 0:100. The average daily gain (ADG) was higher in lambs subjected 50:50 diet, which did not differ from 100:0 but diet 0:100. The feed conversion (FC), feed efficiency (EE) and bionutritional efficiency (EBN) differ between diets (P <0.05), with lambs fed with 0:100 diet more efficient. With regard to gender, CMS and ADG was superior in males (P<0.05). CA, EA were better in males, however when assessing efficiency through the EBN, females were more efficient (P<0.05). 50:50. The lambs diet showed better yields of carcass (P<0.05) in comparison with the others. The percentage of muscle and the muscle: fat ratio was higher in the diet 0:100, which differed from the diet 50:50, and 100:0 diet was similar between diets. The females had better yields of carcass (P<0.05). In the rectus abdominis the intensity of yellow (b *) was greater in the diet 0:100 to 100:0 diet differed, and 50:50 in the diets did not differ. In assessing the subcutaneous fat was obtained difference between diets for L * and b * (P<0.05), lambs 0:100 diet presented lower L * when compared with the others diets. The b * 100:0 in the diet was superior the others diets. In rectus abdominis males had a greater L * and b *. There was no difference between diets for the sensory profile (P>0.05). Was no difference between diets (P<0.05) for alpha-linolenic acid and omega 3 fatty acids in type, these were higher in meat from lambs 100:0 diet (P<0.05), differing from the others. Lamb meat diet 100:0 had lower percentage of monounsaturated fatty acids (P<0.05), compared with the others. The omega ratio n6: n3 was smaller in longissimus dorsi muscle of lambs fed diets 100:0. There was no difference between sexes (P>0.05) for saturated fatty acids (SFA), polyunsaturated (PUFA), monounsaturated acids in the omega-3 type and the PUFA / SFA and omega relations n6: n3 (p>0.05). There was no difference in the diets and sex for the cholesterol content (P>0.05). Thus it is concluded that animals fed the 100% concentrate diet were more efficient, and the diet forage: concentrate ratio (50:50) gave highest carcass yields, and 100% forage diet provided meat with higher levels of acid type of omega-3. The males were less efficient and lower yields of carcass than females.